Acute promyelocytic leukaemia long-term survivors: higher fatigue and greater overall symptom burden. Issue 2 (17th July 2020) - Sommer, Kathrin; Vignetti, Marco; Cottone, Francesco; Breccia, Massimo; Annibali, Ombretta; Luppi, Mario; Intermesoli, Tamara; Borlenghi, Erika; Carluccio, Paola; Rodeghiero, Francesco; Fabbiano, Francesco; Romani, Claudio; et al.
Abstract : Objective: We aimed to investigate the association of fatigue with severity of other key cancer symptoms, as well as symptom interference with daily activities and outlook on life, in long-term survivors of acute promyelocytic leukaemia (APL). Methods: The study sample consisted of APL survivors (n=244), with a median time from diagnosis of 14.3 years (IQR=11.1–16.9 years), previously enrolled in a long-term follow-up study. Symptom severity and symptom interference were assessed using the well-validated MD Anderson Symptom Inventory (MDASI). Fatigue was evaluated with the Functional Assessment of Chronic Illness Therapy-Fatigue questionnaire. Results: Higher fatigue burden was associated with increased affective symptoms, memory problems, drowsiness, sleep disturbances, shortness of breath and pain. Higher levels of fatigue were also associated with higher scores across all interference items of the MDASI. Overall, symptoms interfered most with mood, but among APL survivors with high levels of fatigue, symptoms interfered most with enjoyment of life. Multivariable regression analysis confirmed the independent association between fatigue and all symptom severity items of the MDASI. Conclusions: The current findings show that long-term APL survivors who report higher fatigue also experience a greater overall symptom burden and a substantial impact on performance of daily activities. Further studies are needed to examine whether interventions aimed at reducing fatigue could also reduce overall symptom burden.